Regresi Nonparametrik Spline Truncated untuk Pemodelan Persentase Penduduk Miskin di Jawa Barat Pada Tahun 2021 - Rosse Millania Pichago Firpha; Anneke Iswani Achmad (UNISBA Press, 2022)
Abstract. Nonparametric regression is a statistical method used to model the relationship between response variables and predictor variables whose pattern shape is unknown. In nonparametric regression there are several approaches, one of which is the spline. Spline nonparametric regression, if there is one predictor variable then the regression is called univariable spline nonparametric regression. Conversely, if there is one response variable with more than one predictor variable then the regression is called a multivariable spline nonparametric regression. In nonparametric regression there is a truncated spline model. The truncated spline function is a polynomial function that is dismembered at a knot point. A knot point is a joint fusion point where the function is truncated, or a point that describes a change in data behavior at a certain sub-sub-interval. Therefore, truncated spline models have an excellent ability to handle data whose behavior is arbitrary at certain sub-sub intervals. This study will use truncated spline nonparametric regression to model the number of poor people in West Java in 2021. The data used is secondary data sourced from the publication of the Indonesian Central Statistics Agency (BPS). Abstrak. Regresi nonparametrik adalah suatu metode statistika yang digunakan untuk memodelkan hubungan antara variabel respon dengan variabel prediktor yang tidak diketahui bentuk polanya. Dalam regresi nonparametrik terdapat beberapa pendekatan salah satunya spline. Regresi nonparametrik spline, jika terdapat satu variabel prediktor maka regresi tersebut dinamakan regresi nonparametrik spline univariabel. Sebaliknya, apabila terdapat satu variabel respon dengan lebih dari satu variabel prediktor maka regresi tersebut disebut regresi nonparametrik spline multivariable. Dalam regresi nonparametrik terdapat model Spline Truncated. Fungsi Spline Truncated merupakan fungsi polinomial yang terpotong-potong pada suatu titik knot. Titik knot merupakan titik perpaduan bersama dimana fungsi tersebut terpotong, atau titik yang menggambarkan terjadinya perubahan perilaku data pada sub-sub interval tertentu. Oleh karena itu, model Spline Truncated memiliki kemampuan yang sangat baik untuk menangani data yang perilakunya berubah-ubah pada sub-sub interval tertentu. Pada penelitian ini akan menggunakan regresi nonparametrik Spline Truncated untuk mememodelkan jumlah penduduk miskin di Jawa Barat pada tahun 2021. Data yang digunakan adalah data sekunder yang bersumber dari publikasi Badan Pusat Statistika (BPS) Indonesia.